The Associations of GH and GHR Genes with Carcass Components in Indonesian Kampung and Broiler Chicken Cross - I. Khaerunnisa; Jakaria Jakaria; I. I. Arief; C. Budiman; C. Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2017)
The chicken growth hormone (GH) and its receptor (growth hormone receptor, GHR) play important roles in chicken performances due to their crucial functions in growth. The variations of GH and GHR genes were then thought to be associated with the variations of the performances. This experiment was designed to identify the g.2248G>A GH and the g.565G>A GHR loci polymorphisms and to evaluate their associations with carcass components in Kampung and broiler chicken cross. A total of 215 chickens including 4 chicken populations (Kampung, Cobb broiler, F1, and F2 Kampung x broiler chicken cross) were screened to identify polymorphism using PCR-RFLP technique with EcoRV and Eco72I restriction enzyme for GH and GHR loci, respectively. The carcass components were recorded at 26 weeks of age on F2 Kampung and broiler chicken cross (42 chickens) for association study. Both the g.2248G>A GH and the g.565G>A GHR loci were polymorphic with two alleles (G and A) and three genotypes (GG, AG, and AA). The GG genotype and the G allele of GH locus were predominant in all chicken populations. While in GHR locus, the AA genotype and the A allele were found to be higher in all chicken populations. The association study showed that the g.565G>A GHR locus polymorphism had significant effect on carcass components, including live weight, carcass weight, breast weight, thighs weight, breast muscle weight, and thighs muscle weight. There was no significant association was found between the g.2248G>A GH genotype and carcass components. It could be concluded that the g.2248G>A GH and the g.565G>A GHR loci were polymorphic in Kampung and broiler chicken cross and the g.565G>A GHR locus was accosiated with carcass components. This g.565G>A GHR SNP might be an important candidate marker for chicken growth and muscle mass improvement.